Morphological changes of gums microcapillaries at the exotoxicosis (Experimental biology, 2015)
Ultrastructural study of microvascular blood capillaries of mucous membrane of the gums animals a day after cadmium intoxication showed, thinning of the endothelial lining and swelling of the interstices. Increase in the volume density of granular endoplasmic reticulum by 79%. Also increased bulk density of mitochondria by 40%, which was due to swelling of the data органоидов, evidenced by the decrease of their electron density and decrease the number of Crist. Decreased numerical density attached ribosomes on 54%, free poliribosomes by 60%, and the volume density of the basal mikropinocytosis vesicles on 45%, люминальных by 47%, cytoplasmic vesicle - by 70%. Thus, long action of the chloride cadmium on mucous shell of the gums causes the signifi cant changes to her(its)structure such as, swell hutches, reduction to concentrations organell responsible for protein syntheses and amount drink porosity.
Keywords: blood vessels; gum microcapillaries; endoteliocites; exotoxicosis; cadmium